THE INFLUENCE OF LOCUS OF CONTROL, AUDITOR PERFORMANCE, PROFESSIONAL ETHICS, MACHIAVELLIAN TRAITS AND PROFESSIONAL COMMITMENT ON AUDITOR DYSFUNCTIONAL BEHAVIOR - Khairinisya, Adila Famela; Sosiady, Mulia; Nanda Ria, Bayu Sedih (International Journal of Business and Information Technology, 2026)
This study, a quantitative research aimed at analyzing the influence of locus of control, auditor performance, professional ethics, Machiavellian trait, and professional commitment on dysfunctional audit behavior. The population in this study consisted of 64 auditors working at the Inspectorate Office of Riau Province, with a sample of 60 respondents. The data used were primary data obtained through the distribution of questionnaires to respondents, while the data analysis technique was conducted using SPSS version 30. The results of the study indicate that locus of control and Machiavellian trait have a positive effect on dysfunctional auditor behavior, whereas professional ethics and professional commitment have a negative effect on dysfunctional auditor behavior. Meanwhile, auditor performance does not have a significant effect on dysfunctional auditor behavior.